Illiteracy in the Arab world - Hammoud, Hassan R. (2005)
This article uses data from UNESCO and United Nations Development Programme (UNDP) publications to examine the trends and characteristics of literacy and illiteracy in the Arab countries. The analysis revealed great variations among the Arab countries and the countries are grouped according to their achievements: (1) 'literacy abundant countries', characterised by their limited size, small populations and abundant financial resources; (2) a second group characterised by large geographical areas and limited resources, but with impressive records in combatting illiteracy; and (3) literacy deprived countries', characterised by large populations spread over vast geographical regions and a shortage of financial resources. Girls and women, rural populations, nomads and the disabled have the highest illiteracy levels. The article highlights innovative programs/pilot projects for girls in the Arab region and outlines the challenges and limitations. The article concludes that despite the significant progress made in the field of adult education, in terms of implementing the Education for All (EFA) goals, the Arab region is still below the required level.